374 Volume of contrast to creatinine clearance ratio predicts early mortality and AKI after TAVI. (8th December 2021) - Venturi, Gabriele; Scarsini, Roberto; Pighi, Michele; Sole, Paolo Alberto Del; Mainardi, Andrea; Ribichini, Flavio
Abstract: Aims: The volume of contrast to creatinine clearance ratio (CV/CrCl) is a useful indicator of the risk of acute kidney injury (AKI) in patients undergoing percutaneous interventional procedures. Association between CV/CrCl and adverse outcome after transcatheter aortic valve implantation (TAVI) was suggested but it is not well established. Methods and results: A large retrospective multicentre cohort of 1381 patients treated with TAVI was analysed to assess the association between CV/CrCl and the risk of AKI and mortality at 90 days and one year after TAVI. Patients receiving renal replacement therapy at the time of TAVI were excluded. CV/CrCl was associated with the risk of AKI and 90 days mortality after TAVI after adjustment for age, sex, diabetes, baseline left ventricular function, baseline chronic kidney disease (CKD), previous myocardial infarction and peripheral vascular disease (HR: 1.16, 95% CI: 1.09–1.22, P  < 0.0001). Importantly, CV/CrCl was associated with the adverse outcome independently from the presence of baseline CKD ( p for interaction = 0.22). CV/CrCl was independently associated with the individual components of the composite primary outcome including AKI (OR: 1.18, 95% CI: 1.08–1.28, P  < 0.0001) and 90 days mortality (HR: 1.90, 95% CI: 1.01–3.60, P  = 0.047) after TAVI. AKI (HR: 1.94, 95% CI: 1.21–3.11, P  = 0.006) but not CV/CrCl was associated with the risk of 1-year mortality after TAVI. Conclusions: CV/CrCl is associated with excess renal damage and early mortality after TAVI. Procedural strategies to minimize the CV/CrCl during TAVI may improve early clinical outcomes in patients undergoing TAVI.